RECRUITMENT MANAGEMENT OF NEW EDUCATORS AT SMA NURUL PALEMBANG - Alfiyanto, Afif (Adaara: Jurnal Manajemen Pendidikan Islam, 2022)
The purpose of this study was to determine the implementation of the recruitment of educators at SMA Nurul Amal Palembang. This study uses a type of research that is qualitative. The data collection method in this thesis uses the method of observation, interviews and documentation. The data analysis technique used is data reduction, data presentation and conclusion drawing. The results of this study indicate that the implementation of the recruitment of educators at SMA Nurul Amal has been going well. This can be seen from (1) the planning of the recruitment of educators: a) the formation of a recruitment committee for educators is carried out by deliberation, b) preparing the requirements for new educators to have a diploma and learning certificate, c) the placement of a recruitment committee for educators is arranged based on performance and capabilities. (2) Dissemination: dissemination of information on the recruitment of educators by sharing information through frequently used applications such as Facebook, Instagram and WhatsApp. (3) Acceptance: a) the collection of applicants' application files is done by looking at the criteria of the prospective new educators in accordance with the provisions of the school, b) The process of collecting prospective applicants is based on the specified conditions, then the committee examines them. (4) Selection: a) the selection system is carried out by interviewing and filling out forms, b) the selection process is carried out by the committee by registering, such as looking at educational background, and desired position. c) The school's selection method uses the interview method. The supporting factors for the implementation of the recruitment of educators at SMA Nurul Amal Palembang are: a) facilities, b) collaboration between teams, c) human resources. The inhibiting factors for the implementation of the recruitment of educators at SMA Nurul Amal Palembang are: a) lack of coordination, b) the late formation of an educator recruitment committee.